Governance, risk, and compliance maturity level: Optimizing XX LLC performance achievement - Ayurini, Lovia Wita; Wijayati, Nureni (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This research aims to evaluate the GRC maturity level at XX LLC as an SOE subsidiary engaged in plantation products and provides recommendations to improve GRC implementation. Method: The research was qualitative with a case study approach. Data collection  was carried out using secondary document collection to check the availability of documents to confirm the existence of GRC indicator elements. Supporting evidence that cannot be found on the website will be collected through interviews. The indicator used was from the GRC Forum Indonesia guidelines, which have three aspects. Results: The results obtained from the average calculation of the three aspects of the GRC excellence model in XX LLC were 94.5% or had a proactive maturity level. However, several aspects still need to be improved to maximize GRC implementation at XX LLC and optimize company performance. Conclusions: This study shows that a state-owned plantation subsidiary has reached a proactive GRC maturity level (94.5%), but still needs improvements in strategy dissemination, stress testing, innovation, and HR planning to enhance performance. Limitations: This study is limited to state-owned plantation companies. The number of respondents, sources of theory, and previous research are limited, and access to information is restricted owing to the company policy on confidentiality.   Contribution: Because of the research limitations regarding the GRC maturity level, this study contributes to the literature and serves as an additional reference for further study. For XX LLC, this research can contribute to optimizing the company’s performance. Novelty: This research uses secondary data collection, interviews, and document observation (available or not) as supporting evidence for respondents’ answers through interviews, while other research on GRC maturity levels only uses questionnaires.